MANAGEMENT OF CHILDHOOD STEROID DEPENDENT NEPHROTIC SYNDROME WITH CYCLOPHOSPHAMIDE - AN EXPERIENCE AT AYUB TEACHING HOSPITAL, ABBOTTABAD - shah, syed sajid Hussain; Aalia, Bibi; Ali Raza,; Shahzad Najeeb,; Anis ur Rehman, (Journal of Ayub Medical College Abbottabad, 2021)
Background: This study has been done in children with Steroid dependent nephrotic syndrome (SDNS) to check for the response to cyclophosphamide and relapse on follow up for one year after completion of treatment. Methods: This study was conducted over two years and nine months. Patients were taken as steroid dependent when there were two consecutive relapses occur on steroids tapering or within two weeks of stopping treatment. Children of either sex between ages of 1-14 years, diagnosed case of SDNS were included in this study. Renal biopsy was not done in any patient. After achieving remission with oral steroids, cyclophosphamide was given after calculation of maximum cumulative dose 168 mg/kg for 8 - 12 weeks along with oral steroids. Follow up done every two weeks till completion of treatment for response and adverse effects and thereafter for one year. Results: There were 31 patients, 23 (74.2%) male and 8 (25.8%) females. Age ranged from 1.5 years to 11 years with mean age 5.44±2.39 years. There was full response to cyclophosphamide as none of patient had proteinuria on cyclophosphamide therapy. After completion of cyclophosphamide course, four patients (12.9%) relapsed on follow up while 87.9% remain in complete remission. Only one female patient (3.23%) had adverse effect in form of hair fall and she recovered after completion of treatment. None of patient showed any other adverse effect including haematuria. Conclusion: Cyclophosphamide is an effective therapy in management of childhood SDNS with minimum adverse effects in medium term